Using Robotics to Quantify Impairments in Sensorimotor Ability, Visuospatial Attention, Working Memory, and Executive Function After Traumatic Brain Injury. Issue 4 (July 2018) - Logan, Lindsey M.; Semrau, Jennifer A.; Debert, Chantel T.; Kenzie, Jeffrey M.; Scott, Stephen H.; Dukelow, Sean P.
Abstract : Objective: To investigate the use of a robotic assessment tool to quantify sensorimotor, visuospatial attention, and executive function impairments in individuals with traumatic brain injury (TBI). Setting: Foothills Hospital (Calgary, Canada). Participants: Twenty-three subjects with first-time TBI in the subacute to chronic phase participated in this study. Normative data were collected from 275 to 494 neurologically intact control subjects for each robotic task. Design: A prospective observational case series. Subjects with TBI completed brief clinical cognitive and motor assessments followed by robotic assessments of upper limb reaching, position sense, bimanual motor ability, attention, and visuospatial skills. Scores of subjects with TBI were compared with normative data. Main Measures: Robotic task performance was computed for each subject on each task, as well as performance on specific task parameters. Clinical assessments included the Montreal Cognitive Assessment, Fugl-Meyer upper extremity assessment, and Purdue Peg Board. Results: Subjects with TBI demonstrated a variety of deficits on robotic tasks. The proportion of TBI subjects who were significantly different from controls ranged from 36% (dominant arm reaching) to 60% (bimanual object hitting task). Conclusion: Robotic measures allowed us to quantify a range of impairments specific to each subject, and offer an objective tool with which to examine these abilities after TBI. Abstract : Supplemental Digital Content is Available in the Text.